Association Between Self-Perceived General Human-Likeness During Walking and Walking Speed in Stroke Patients: A Preliminary Study. (July 2022) - Hayashida, Kazuki; Nakazono, Ryota; Yamamichi, Nami; Narita, Masa; Onishi, Koichiro; Morioka, Shu
The difference between the walking speeds of stroke patients and the general population may influence the self-perception of patients, who perceive their walk as lacking general human-likeness. Perception toward human-likeness during walking is defined here as the feeling that one can walk as intended, just like healthy people. Such negative subjective experiences may curb their social participation. However, the perception associated with walking speed in stroke patients is poorly understood. The main purpose of this study was to investigate the relationship between walking speed and perception toward general human-likeness during walking in stroke patients. Thirty-two post-stroke patients were enrolled in this cross-sectional study. Patients performed 10-m walk tests at comfortable and fast speeds and answered questions about their perceived human-like walking after completing the walk ("How much did you feel your walking resembled the human-likeness during walking of general people?"). We found a significant positive correlation between perception toward human-likeness during walking and walking speed at both comfortable and fast speeds. To the best of our knowledge, this report is the first to suggest that walking speed may correlate with self-perception. Our findings may help understand the underlying mechanism in patients perceiving less human-likeness during walking.